Integrating of Aqueous Enzymolysis with Ethanolic Ultrasonication to Ameliorate Cordycepin Content from Vietnamese Cordyceps militaris and Biological Analysis of Extracts. Issue 1 (5th January 2021) - Thanh, Vuong Hoai; Le Thao My, Phan; Do Dat, Tran; Viet, Nguyen Duc; Phuc, Nguyen Cao Minh; Thao, Ngo Hong; Nam, Hoang Minh; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: In this study, the employment of aqueous enzymolysis using alcalase with ethanolic ultrasonication extraction method was investigated. The cordycepin content was analyzed by using reversed‐phase high‐performance liquid chromatography with a diode array detector. The result showed that the highest cordycepin content of 0.4365±0.0309 mg/g could be obtained under extraction conditions including total enzyme volume of 240 μL, incubation time of 50 min, incubation temperature of 55 °C, and ultrasonic power of 840 W. The comparative studies of antioxidant activities of the extract were determined in terms of the DPPH free radical scavenging assay, ferric ion reducing power assay, and H2 O2 scavenging assay. Additionally, the MTT assay was conducted to evaluate the anticancer activities of the extract, illustrating the cytotoxic property against Hep‐G2 cancer cells with the half‐maximal inhibitory concentration (IC50 ) value of 12.20±0.03 μg/mL compared to that of 0.36±0.03 μg/mL for ellipticine, MCF‐7 cancer cells with the IC50 value of 11.60±0.09 μg/mL compared to that of 0.51±0.04 μg/mL for ellipticine, and Lu cancer cells with the IC50 value of 34.50±0.25 μg/mL compared to that of 0.32±0.03 μg/mL for ellipticine. Abstract : This research illustrates the procedure of employing ultrasonication and enzymolysis assisted extraction method for cordycepin extraction from Vietnamese C. militaris . Various influential processing parameters such as pH, total enzyme volume, incubation time, incubation temperature, ultrasonic time, and ultrasonic power on cordycepin content were investigated to optimize the extraction process. Additionally, the extracts under optimal conditions were used to determine antioxidant and anticancer properties for futuristic uses as medicinal drugs.